Ascorbic acid supplementation partially prevents the delayed reproductive development in juvenile male rats exposed to rosuvastatin since prepuberty - Leite, Gabriel Adan Araújo; Figueiredo, Thamiris Moreira [UNESP]; Sanabria, Marciana [UNESP]; Dias, Ana Flávia Mota Gonçalves [UNESP]; Silva, Patrícia Villela e [UNESP]; Martins Junior, Airton da Cunha; Barbosa Junior, Fernando; Kempinas, Wilma De Grava [UNESP] (Elsevier, 2017)
Dyslipidemias are occurring earlier in the population due to the increase of obesity and bad eating habits. Rosuvastatin inhibits the enzyme HMG-CoA reductase, decreasing total cholesterol. Ascorbic acid is an important antioxidant compound for male reproductive system. This study aimed to evaluate whether ascorbic acid supplementation may prevent the reproductive damage provoked by rosuvastatin administration at prepuberty. Male pups were distributed into six experimental groups that received saline solution 0.9%, 3 or 10 mg/kg/day of rosuvastatin, 150 mg/day of ascorbic acid, or 150 mg/day of ascorbic acid associated with 3 or 10 mg/kg/day of rosuvastatin from post-natal day (PND) 23 until PND53. Rosuvastatin-treated groups showed delayed puberty installation, androgen depletion and impairment on testicular and epididymal morphology. Ascorbic acid partially prevented these reproductive damages. In conclusion, rosuvastatin exposure is a probable risk to reproductive development and ascorbic acid supplementation may be useful to prevent the reproductive impairment of rosuvastatin exposure.
Keywords: Ascorbic acid; Male reproduction; Puberty; Rosuvastatin; Testis and epididymis